The Political Economy of Climate Change Policy in the EU: Auction and Grandfathering - Urs Steiner Brandt; Gert Tinggaard Svendsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2003)
Based on the political support function model by Hillman (1982), we consider the choice of policy instruments in environmental regulation. More specifically, we extend the Hillman model so that it can incorporate the connection between the relative strength of lobby groups, the chosen level of regulation and the choice of instrument to facilitate the achievement of this level. We apply this model to explain the shift from auction to grandfathered emission trading in the EU. When explaining this shift in policy, we focus on climate change policy and the three main interest groups, namely industry, consumers and environ-mentalists. From a pure economic point of view, taxation or auctions are clearly preferable to grandfathering. However, from our political economy model, the opposite conclusion might emerge, suggesting the counter-intuitive result that grandfathering, compared to taxation and auction, might give a stronger pres-sure to increase the emission target level.
Keywords: Q28; H2; H4; 330; Political support function; political economy; environmental regula-tion; lobbyism; rent-seeking; taxation; auction; grandfathering; emission trad-ing; European Union; interest groups; industry; consumers; environmentalists; Internationale Umweltpolitik; Klimawandel; EU-Staaten; EU-Umweltpolitik; Emissionshandel